THE CORRELATION OF TWO MONTHS FULL OF BREASTFEEDING ON EARLY INITIATED BREASTFEEDING GROUP WITH PUERPERIUM BLEEDING - Masta, Putu Cantika Jenise Asri; Prabantoro, Benedictus Triagung Ruddy; Pangemanan, Lisa (JOURNAL OF WIDYA MEDIKA JUNIOR, 2022)
Background: Postpartum bleeding is one of the main causes of mortality in mothers in 2017. Based on Profil Kesehatan Provinsi Jawa Timur's data in 2017, about 28,26% of mothers' mortality percentage is because of postpartum bleeding. Some of the factors affecting the duration of puerperium bleeding are the initiation of early breastfeeding and exclusive breastfeeding. Early breastfeeding initiation can stimulate the oxytocin hormone to contract the uterine and help complete the extrusion of the placental site and sloughing of decidua tissue (lochia). Objective: This study aims to know the correlation of 2 months full of breastfeeding on early initiated breastfeeding group with puerperium bleeding. Method: This study is an observational analytical study where the design is cohort retrospective, and the 60 samples used in this research are taken with simple random technique sampling. This research was carried out by collecting information from secondary data, and the whole process was done in Gotong Royong Hospital Surabaya from July to September 2020. This research used the Mann-Whitney U test to analyze and find the correlation of both variables. Results: Based on the statistic test, there is no correlation between both variables, resulting in p = 0,211. Conclusion: there is no significant correlation between 2 months full of breastfeeding on the early initiated breastfeeding group with puerperium bleeding.